-9(-3t+8)=-13t+48

Simple and best practice solution for -9(-3t+8)=-13t+48 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9(-3t+8)=-13t+48 equation:


Simplifying
-9(-3t + 8) = -13t + 48

Reorder the terms:
-9(8 + -3t) = -13t + 48
(8 * -9 + -3t * -9) = -13t + 48
(-72 + 27t) = -13t + 48

Reorder the terms:
-72 + 27t = 48 + -13t

Solving
-72 + 27t = 48 + -13t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '13t' to each side of the equation.
-72 + 27t + 13t = 48 + -13t + 13t

Combine like terms: 27t + 13t = 40t
-72 + 40t = 48 + -13t + 13t

Combine like terms: -13t + 13t = 0
-72 + 40t = 48 + 0
-72 + 40t = 48

Add '72' to each side of the equation.
-72 + 72 + 40t = 48 + 72

Combine like terms: -72 + 72 = 0
0 + 40t = 48 + 72
40t = 48 + 72

Combine like terms: 48 + 72 = 120
40t = 120

Divide each side by '40'.
t = 3

Simplifying
t = 3

See similar equations:

| 2e+6=3e-1 | | 1/2(k-5)=3 | | 4-8=3-5+n | | 7(-3x+7)=-(-3x+-73) | | 2x+43=34 | | M+14=3M-8 | | x^3+5x^2=6x | | m+7+4=-8 | | 5(x-7.2)=14.5 | | -(3x+2)=-19x+62 | | 25.748=2*3.14*r^2+2*3.14*r*3.1 | | 5a+10b=450 | | 453.6672=2*3.14*r^2+2*3.14*r*13 | | 5b+10a=450 | | -1-0.28v=2 | | 5*26=x | | -5+3(6-x)=1 | | 4x*3=99+x | | 20x=.6 | | 10a+5b=450 | | -2(6p-5)+2p=8p-8 | | 2(0,3x-1)-0,6=4+0,1x | | 8+10y=9y-6 | | -16t^2+57=0 | | 17x=6x-22 | | 138-4x=32x+22 | | 10.5=3b-12.5 | | 4x+2x+96-22=88+4x | | 6-3x-5x-1=10 | | 4(3x-44)=4(2x-10) | | 4x^4-17x^2+18=0 | | 5x*3+17=69+2x |

Equations solver categories